30-Day Emergency Department Visits After Primary Lumbar Fusion: Incidence, Causes, Risk Factors, and Costs. Issue 3 (April 2019) - Jain, Nikhil; Brock, John L.; Phillips, Frank M.; Weaver, Tristan; Khan, Safdar N.
Abstract : Our objective was to describe the incidence, causes, risk factors, and costs associated with 30-day emergency department (ED) visits after primary lumbar fusion. A national insurance database was retrospectively analyzed to study patients with primary lumbar fusions performed for degenerative pathology of the spine between 2007 and Q3-2015. Risk factors for ED visits, and ED to hospital transfer were studied using multiple-variable logistic regression analysis. Our cohort included 37, 559 patients with a mean age of 66.0±10.0 years. A total of 4806 (12.8%) patients had 10, 281 ED visits within 30 days after surgery. Of these, 945 (19.9%) had multiple (≥3) visits, and 1466 (30.5%) were admitted to the hospital for management. Common causes for presentation in the ED were cardiorespiratory complaints (49.4%, n=2377), and back and/or leg pain (47.7%, n=2294). Risk factors for all ED visits, multiple ED visits, and hospital admission from the ED have been identified. The overall ED cost burden was nearly two-thirds as much as hospital readmissions within 30 days (6, 994, 260 vs. 10, 880, 999). There is a sizable subset of patients that present to the ED for acute care but do not require hospitalization. Causes and risk factors for presentation in patients with multiple ED visits are somewhat different than patients requiring hospital readmission. Abstract : Supplemental Digital Content is available in the text.